Perbedaan Efektivitas Zeolit dan Manganese Greensand untuk Menurunkan Kadar Fosfat dan Chemical Oxygen Demand Limbah Cair “Laundry Zone” di Tembalang - Dahona Lenthe Lavina; Sulistyani Sulistyani; Mursid Rahadjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Laundry business is a business in clothes washing services. Preliminary test results show that the levels of phosphate and COD laundry liquid wastes is 12,36 mg/l and 5.920 mg/l. These levels exceeded the water quality standard of waste that phosphate concentration of 2 mg/l and COD concentration of 100 mg/l. This research aimed to determine the difference effectiveness of zeolite and manganese greensand to decrease phosphate and chemical oxygen demand on waste